Two‐Tailed RT‐qPCR for the Quantification of A‐to‐I‐Edited microRNA Isoforms. Issue 1 (23rd January 2023) - Voss, Gjendine; Ceder, Yvonne
Abstract: MicroRNAs are short non‐coding RNAs with important functions in the regulation of gene expression in healthy and diseased tissues. To optimally utilize the biological and clinical information that is contained in microRNA expression levels, tools for their accurate and cost‐effective quantification are needed. While the standard method, qPCR, allows for quick and cheap microRNA quantification, specificity is limited due to the short lengths of microRNAs and the high similarity between closely related microRNA family members. A‐to‐I editing can further diversify the microRNA pool by altering individual nucleotides. There is currently a lack of protocols for the accurate quantification of A‐to‐I‐edited microRNA isoforms using qPCR. Here, we describe a protocol to quantify microRNA editing isoforms using two‐tailed RT‐qPCR, with either SYBR Green or hydrolysis probes. The user will perform reverse transcription of RNA samples, generate standard curves, and quantify the resulting cDNA in the following qPCR step. We also give guidelines for primer design and for the evaluation of assays using synthetic oligonucleotides. These tools are expected to be transferable to any A‐to‐I‐edited microRNA and its isoforms. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Two‐tailed reverse transcription of A‐to‐I‐edited microRNAs Basic Protocol 2 : SYBR Green‐based qPCR for A‐to‐I‐edited microRNAs Alternate Protocol : Hydrolysis probe‐based qPCR for A‐to‐I‐edited microRNAs Support Protocol : Preparation of standard curves using synthetic RNA oligonucleotides